Indonesia responsibility on sea pollution caused by coal waste (study on Bengkulu river pollution) - Ema Septaria (Proceedings of AICS - Social Sciences, 2013)
Bengkulu, which is located on coastal area and is adjoining directly with Hindia Ocean, is one of provinces of Indonesia having a potential coal resource quality. In exploring and exploiting this resource, district government of Bengkulu has issued licenses to some companies.Unfortunately the activities of some company caused damage and pollution on headwaters and downstream of Bengkulu river basin at coastal area.Supposing it is not coped with soon by the government, the waste of the coal which caused damage and pollution will continue flow to the sea and gradually will empty into Hindia Ocean.The activities that affect the damage of river and sea environment ecosystem will make Indonesia be responsible internationally.It is due to Indonesia has been agreed to be bound to United Nations Convention on The law of the Sea (UNCLOS) 1982. Notwithstanding UNCLOS 1982 gives right to states to exploit their natural resources pursuant to their environmental policies and in accordance with their duty to protect and preserve the marine environment, on the other side it lays obligation to protect and preserve the marine environment. State shall take, individually or jointly as appropriate all measures consistent with UNCLOS that are necessary to prevent, reduce and control pollution of the marine environment from any source, using for this purpose the best practicable means at their disposal and in accordance with their capabilities, and they shall endeavor to harmonize the policies in this connection. States also shall take all measures necessary to ensure that activities under their jurisdiction or control are so conducted as not to cause damage by pollution to other States and their environment, and that pollution arising from incidents or activities under their jurisdiction or control does not spread beyond the areas where they exercise sovereign rights in accordance with UNCLOS 1982.If the District Government of Bengkulu does not pay attention to this problem, Indonesia will internationally be responsible for putting back the sea environment to the condition before the pollution took place. This responsible will take long time and much fund. It will also make Indonesia’s credibility in international society goes down as they will value Indonesia does not care about its own environtment, especially international sea environtment. For that, it needs to provide preventive action soon by the district government, for being apart from responsibilities and for protecting the citizen right on health environtment.Keywords: Indonesia Responsibility, Sea Pollution, Coal Waste.